So we have:
![-3a^5b^2\sqrt[3]{a^2c}](https://img.qammunity.org/2023/formulas/mathematics/college/z65kxa6naxuio1ck11kmb2xqf4mfcpqj9s.png)
And we want to knowthe original before simplification, that is, before evaluating the interior part of the root.
So, we need to figure a way to put the part outside of the root back in.
Taking the cubic root of a number is the same as dividing its exponent by 3, because:
![\sqrt[3]{a^n}=a^{(n)/(3)}](https://img.qammunity.org/2023/formulas/mathematics/college/isebxm5a7zo2r23hh8qdbrmo3uh4yzysf6.png)
So, thinking in the other direction, we need to multiply the exponents by 3 before taking it back to the inside of the cubic root:
![a^k=a^{(3k)/(3)}=\sqrt[3]{a^(3k)}](https://img.qammunity.org/2023/formulas/mathematics/college/vtqxggkk070zo3hkqfytj3i40tipm7jik9.png)
So, the b part have a 2 in the exponent, so we can multiply it by 3 to get 6:
![\begin{gathered} b^2=b^{(3\cdot2)/(3)}=\sqrt[3]{b^(3\cdot2)}=\sqrt[3]{b^6} \\ -3a^5b^2\sqrt[3]{a^2c}=-3a^5\sqrt[3]{b^6}\sqrt[3]{a^2b^(3\cdot2)c}=-3a^5\sqrt[3]{a^2b^6c} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nicuu7uqcdqi2iab4s87fsims9zwm5mspl.png)
The a part have a 5 in the exponent, so we will get 15:
![\begin{gathered} a^5=a^{(3\cdot5)/(3)}=\sqrt[3]{a^(3\cdot5)}=\sqrt[3]{a^(15)} \\ -3a^5\sqrt[3]{a^2b^6c}=-3\sqrt[3]{a^(15)}\sqrt[3]{a^2^{}b^6c}=-3\sqrt[3]{a^2a^(15)b^6c} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gckl9axwbjr0auwmigudkgltzxio7hnh8f.png)
Now, since we have a² and a¹⁵, we can add their exponents:
![\begin{gathered} a^2a^(15)=a^(17) \\ -3\sqrt[3]{a^2a^(15)b^6c}=-3^{}\sqrt[3]{a^(17)b^6c} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qhsq5rnw9dknagxuc07lz0pc76a34mq12g.png)
Now, the -3 have an exponent of 1, so:
![\begin{gathered} -3=(-3)^1=(-3)^{(3\cdot1)/(3)}=\sqrt[3]{(-3)^(3\cdot1)}=\sqrt[3]{(-3)^3}=\sqrt[3]{-27} \\ -3^{}\sqrt[3]{a^(17)b^6c}=\sqrt[3]{-27}^{}\sqrt[3]{a^(17)b^6c}=^{}\sqrt[3]{-27a^(17)b^6c} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/68hyac9vy63kos6qlie4j4l111hlulnzo3.png)
Thus, we have, in the end:
![^{}\sqrt[3]{-27a^(17)b^6c}=-3a^5b^2^{}\sqrt[3]{a^2^{}c}](https://img.qammunity.org/2023/formulas/mathematics/college/s1upi56fscoaywh1lfyaw4bn5527eewza5.png)